2019
DOI: 10.3329/jbau.v17i2.41936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerated and non-aerated compost tea against some fungal phytopathogens

Abstract: Suppressive effect of aerated and non-aerated compost tea against different fungal phytopathogens, namely Alternaria solani, Bipolaris sorokiniana, Fusarium oxysporum, Pestalotia palmarum and Sclerotium rolfsii was evaluated in Plant Protection Laboratory of Agrotechnology Discipline, Khulna University, Khulna, Bangladesh during 2016. Commercial compost, “Rastic Joibo Shar” was used to prepare aerated and non-aerated compost teas at 20% and 25% concentrations. All the treatments significantly inhibited the myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…After 7 days of storage, the total phenolics and flavonoids and the antioxidant capacity were significantly lower than at harvest time, as was observed by Kalt et al 1999 [68], Serafini et al 2002 [69] and Ninfali and Bacchiocca 2005 [70]. The decrease in total phenolics that occurs during storage may be due to increased antioxidant enzymatic activities [71]. However, other authors found that total flavonoids remained quite constant in spinach [72] and the phenolic contents increased in lettuce [73].…”
Section: Discussionmentioning
confidence: 61%
“…After 7 days of storage, the total phenolics and flavonoids and the antioxidant capacity were significantly lower than at harvest time, as was observed by Kalt et al 1999 [68], Serafini et al 2002 [69] and Ninfali and Bacchiocca 2005 [70]. The decrease in total phenolics that occurs during storage may be due to increased antioxidant enzymatic activities [71]. However, other authors found that total flavonoids remained quite constant in spinach [72] and the phenolic contents increased in lettuce [73].…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, both biochar and vermicompost are able to influence the physical and chemical properties of growth media. Biochar being a carbon sequester, has several beneficial effects on soil properties, such as increased water holding capacity (Karhu et al, 2011), enhanced cation exchange capacity (CEC) as well as base saturation (BS) (Yuan and Xu, 2011), In addition to this, vermicompost alters both nutritional and microbial status of media (Islam et al, 2019). The composition of biochars and vermicompost in the growth media of the present study was selected arbitrarily and not optimized with respect to the needs of a Cabbage.…”
Section: Resultsmentioning
confidence: 99%
“…For the present study, the focus is compost tea amendments from vermicompost. Compost tea is a method that utilizes compost or vermicompost to brew with nutrients and microbial starter cultures to increase biological activity (Lim et al, 2016;Islam et al, 2019).…”
Section: Compost Vermicompost and Compost Teamentioning
confidence: 99%
“…The majority of literature relating to compost tea is focused on the methods of creating compost tea, the pathogens potentially present in various methods, and the results on soil and plant health (De Corato, 2020;Mengesha et al, 2017;Islam et al 2019). Research on the relationship between compost tea and GHG emissions is limited, but there is a significant amount of research on the impact of compost on GHG emissions.…”
Section: Compost Vermicompost and Compost Teamentioning
confidence: 99%